2023
DOI: 10.1111/jar.13111
|View full text |Cite
|
Sign up to set email alerts
|

From mainstream employment to mainstream retirement: A randomised controlled trial of a transition to retirement intervention for adults with intellectual disability

Abstract: Background: We evaluated a transition to retirement intervention that adapted strategies used to support employment of people with intellectual disability in mainstream workplaces. The intervention facilitated their independent participation in mainstream community groups and volunteering.Methods: We randomised 29 older Australians who currently/previously worked in mainstream employment into an intervention group or wait-list control group. Hours of independent participation in target activities were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our findings highlight the need for an increased focus on retirement planning that is person-centered supports individual choice (Brotherton, 2022;Brotherton et al, 2020). Some participants retired in their mid-forties, so this planning should begin early.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our findings highlight the need for an increased focus on retirement planning that is person-centered supports individual choice (Brotherton, 2022;Brotherton et al, 2020). Some participants retired in their mid-forties, so this planning should begin early.…”
Section: Discussionmentioning
confidence: 76%
“…Bill's view that "I've got the years in," and Robert's 70th birthday are examples. Australian retirement research has reported similar findings (Brotherton, 2022;Brotherton et al, 2020).…”
Section: Milestonesmentioning
confidence: 70%
See 1 more Smart Citation
“…The Keeping Active intervention supported 19 of 22 (86%) participants to independently engage in a mainstream leisure group or customised volunteering role of their choice, with 77% of these continuing to participate in their selected activity after 12 months. The study evaluation included a randomised controlled trial, showing that compared to those in a wait-list control group (n = 17), intervention participants (n = 12) had a significantly increased level of independent mainstream community group or volunteering participation after 13 weeks [27]. These findings highlight the potential for existing employment support strategies to be applied to supporting older workers with intellectual disability in their preparation for and transition to retirement from mainstream employment.…”
Section: Transition To Retirement From Mainstream Employmentmentioning
confidence: 98%
“…In response to these issues, an Australian intervention model, Keeping Active, similar to the active mentoring approach mentioned previously, was developed. The aim was to facilitate independent participation in mainstream community activities as part of developing a retirement lifestyle for people with intellectual disability transitioning from mainstream employment [27]. This approach adapted the employment support strategies used by the DES Jobsupport program described earlier in this paper and differed from the programs mentioned so far, which were all developed for older workers retiring from sheltered employment.…”
Section: Transition To Retirement From Mainstream Employmentmentioning
confidence: 99%